Exploring Curriculum Implementation Needs Based on Self-Determination Theory: A Case Study in Indonesia Primary School Teachers - Herlina; Surya; Rusmayadi; Bachtiar, Muhammad Yusri; Samputri, Salma; Rahayu (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2025)
Student disengagement and low intrinsic motivation remain persistent issues in educational contexts, often due to rigid curriculum structures that overlook learners' psychological needs. This study aims to analyze the operational curriculum needs of primary school teachers in fostering student autonomy, motivation, and engagement, using Self-Determination Theory (SDT) as the theoretical foundation. Employing a qualitative phenomenological approach, the study involved 12 private primary school teachers in Makassar, Indonesia. Data were collected through semi-structured, in-depth interviews and analyzed thematically to explore strategies and perceptions related to SDT-based curriculum implementation. The results revealed three key themes: recognizing individual student characteristics, offering meaningful choices in learning activities to support autonomy, and maintaining strong communication with parents to create a collaborative and emotionally supportive learning environment. These strategies were reported to significantly enhance student participation, classroom inclusivity, and a sense of belonging. The study concludes that integrating SDT principles into operational curriculum planning not only increases student engagement but also contributes to the development of a more holistic and humanistic learning atmosphere. This research contributes to the field of motivation-oriented curriculum design and offers practical implications for educators and school leaders in developing student-centered instructional practices. Further studies using quantitative or mixed methods are recommended to validate and expand these findings across broader educational contexts and grade levels.